PHRASEOLOGY OF RUSSIAN AND UZBEK LANGUAGES AS AN ELEMENT OF CULTURAL EXPRESSION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Phraseologisms are one of the basic units of the language, carrying national and cultural elements. Comparison of phraseological units of the Russian and Uzbek languages helps to identify the different values inherent in these peoples, and plays an important role in the development of anthropocentrism, one of the main paradigms today. The article provides a comparative analysis and research of some phraseological units of the Russian and Uzbek languages.